2020
DOI: 10.1002/jor.24937
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen treatment inhibits articular cartilage loss in a rat model of osteoarthritis

Abstract: The effects of naproxen, a nonsteroidal anti-inflammatory drug (NSAID), on articular cartilage degeneration in female Sprague-Dawley rats was examined. Osteoarthritis (OA) was induced by destabilization of the medial meniscus (DMM) in each knee. Rats were treated with acetaminophen (60 mg/kg), naproxen (8 mg/kg), or 1% carboxymethylcellulose (placebo) by oral gavage twice daily for 3 weeks, beginning 2 weeks after surgery. OA severity was assessed by histological Osteoarthritis Research Society International (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In our study, we observed chondroprotective effects of NPX treatment using histological staining (Figure 7e ), which agrees with a recent study where NPX treatment was found to reduce the loss of articular cartilage in the rat DMM model. [ 46 ] However, the transcriptome in chondrocytes was not significantly influenced by NPX, supporting the findings by Mastbergen et al. [ 44 ] Instead of playing a direct role on chondrocytes, naproxen may function through suppressing the inflammation of “synovial tissue” in the miniJoint and reducing the release of pro‐inflammatory cytokines and degradative enzymes to the SM (Figure 7c ).…”
Section: Discussionsupporting
confidence: 80%
“…In our study, we observed chondroprotective effects of NPX treatment using histological staining (Figure 7e ), which agrees with a recent study where NPX treatment was found to reduce the loss of articular cartilage in the rat DMM model. [ 46 ] However, the transcriptome in chondrocytes was not significantly influenced by NPX, supporting the findings by Mastbergen et al. [ 44 ] Instead of playing a direct role on chondrocytes, naproxen may function through suppressing the inflammation of “synovial tissue” in the miniJoint and reducing the release of pro‐inflammatory cytokines and degradative enzymes to the SM (Figure 7c ).…”
Section: Discussionsupporting
confidence: 80%
“…27 Similarly, cultured cartilage explants harvested from patients who used NSAIDs daily for 4 weeks before total joint replacement surgery had increased proteoglycan synthesis rates compared with those who did not receive NSAIDs. 7 Preclinical studies using instability 37 and collagenase-induced 20 OA rodent models observed decreased damage when treating animals with naproxen. Disease modification with NSAID use, however, has not yet been observed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery rats were anesthetized with intraperitoneal injection of 5% xylazine and 1% ketamine. 8 Right knee joint of rats was shaved and disinfected in a sterilized environment. After that, a para-patellar incision was made on medial side for complete joint exposure.…”
Section: Methodsmentioning
confidence: 99%